Corresponding changes in kynurenine hydroxylase activity, membrane fluidity, and sterol composition in Saccharomyces cerevisiae mitochondria. - McLean-Bowen, C A (1981)
The effect of sterol composition on the properties of the mitochondrial membrane of Saccharomyces cerevisiae was investigated. The physical state of mitochondrial membranes from wild-type strains and sterol mutants was compared, using a fluorescence polarization technique with 1,6-diphenyl-1,3-5-hexatriene. Changes in the rate of depolarization of the probe molecule as a function of temperature suggest the occurrence of a phase transition in the mitochondrial membranes isolated from the sterol mutants but not in the membranes isolated from the wild types. Arrhenius kinetics of the mitochondrial membrane-bound enzyme L-kynurenine-3-hydroxylase exhibited changes in activation energy at temperatures similar to those observed in the fluorescence polarization study. The ratio of mitochondrial sterol to phospholipid and the phospholipid fatty acid composition of the organisms were characterized.